Citizen brief: Developing a Type 1 diabetes screening program in Canada - Wilson, MG; Scallan, Eilish; Hayeems, R; Bain, T; Velez, CM (My University, 2024)
A plain-language synthesis of what is known based on the best available global and local research evidence about the problem(s) related to developing a Type 1 diabetes screening program in Canada, elements of a potentially comprehensive approach for addressing it, and key implementation considerations. This citizen brief was prepared to inform 5 citizen panels.
Keywords: Type 1 diabetes; screening program; Canada